A review of use of the word 'flare' in hidradenitis suppurativa studies. (1st January 2020) - Kirby, J.S.; Moore, B.; Leiphart, P.; Shumaker, K.; Mammis‐Gierbolini, A.; Benhadou, F.; del Marmol, V.
Summary: Hidradenitis suppurativa (HS) causes red, painful, draining bumps and tunnels in the skin. About 0.1 to 1% of people have HS in the U.S.A. and Europe. HS is more common in females. HS lesions (affected areas) happen mostly in folds of the body, such as the armpits, under the breast, groin, or buttocks. The lesions can come‐and‐go or last for months or years. HS can have times where it is worse than usual. These have been called 'flares'. To measure flares in future studies, a definition for a flare is needed. This study was done to find out how flares were defined in past studies. The researchers looked in a database of published articles for studies about HS that mentioned the word 'flare' or 'exacerbation'. The researchers found 274 published studies, and 154 of them were good enough to be included in this study. Twenty‐seven studies had the word 'flare' and 16 included the word 'exacerbation.' Only two studies included a definition for the word 'flare' and only one paper had a definition for the word 'exacerbation.' The way to measure a flare (or exacerbation) was by the patient's experience or the clinician's exam of the skin. This review study showed that an HS flare is often not defined in studies, and the definitions are not always the same. A better definition of HS flare needs to be made so that people with HS, clinicians, and researchers can better measure the activity of the HS and the impact of treatments. This summary relates to the study: A narrative review of the definition of 'flare' in hidradenitis suppurativa